MEDICAL CONSULTANCY OF THE FIRST TURKISH ANTARCTIC RESEARCH EXPEDITION 2016 - (:unkn) unknown (ISTANBUL UNIV, FACULTY MEDICINE, PUBLISHING OFFICE, 2016)
Objective: Antarctica is the coldest, farthest, and highest continent on Earth. Due to its extreme conditions and isolation, researchers undergo health assessments, which are prepared differently in each country. Health standards for National Arctic and Antarctic Polar Research Projects were prepared by our Faculty, and the scientists participating in the first national scientific expedition were assessed in the Department of Underwater and Hyperbaric Medicine. Materials and Methods: After one year of investigation, National Turkish Polar Research Health Standards (TUKAS) were prepared. Medical assessment of the candidate researchers was done according to these standards in our hospital. All the physical examinations, laboratory and radiologic results were recorded. Researchers were monitored all through the expedition and any medical condition was recorded. Results: Thirteen researchers attended the 1st Turkish Antarctic Scientific Expedition in 2016. Twelve researchers were assessed according to TUKAS. Cardiologic conditions were detected in four applicants. There was a history of tuberculosis in one applicant and hepatitis A and B in another. Also, there were minor gastrointestinal problems in three applicants. None of the detected conditions impeded participation. No serious health problems were reported during the expedition. Conclusion: Team members who are to work in Antarctica should be selected carefully by taking into account a physical examination and medical conditions. Istanbul Faculty of Medicine, Department of Underwater and Hyperbaric Medicine has been selected for the examination of the Turkish team. Thus, the data, which will be kept in one center, will be an important resource for future scientific studies.
Keywords: Antarctic regions; demography; health condition